Persona in spe. Anthropological and Theodical Aspects of Hope - Arkadiusz Gudaniec (Religions, 2021)
I intend to reflect on three phenomena that are revealed in the personal experience of hope: (1) hope distinguishes a person from the natural context, but it does so through nature, i.e., based on desires rooted in human nature; (2) hope is not only inscribed in the existential situation of human being, but also expresses the very meaning of human transcendence: the person transcends themself, because they live the hope of fulfillment in the transcendent reality; hope is a foretaste of a higher, more perfect life; (3) hope is a person’s deeply experienced expectation of love, that is, of someone who loves. The above phenomena require a justification, which is the answer to the question “what is the reason for experiencing hope?”. Carrying out analyses on the basis of the modernized metaphysics of the person, I refer primarily to the concept of personal acts, to the concept of religiosity as an essential property of the person and to elements of the concept of love. The conclusions of these analyses indicate the necessity of accepting the real existence of the object of human hope, since personal life essentially goes beyond contingency, towards wholeness in the form of union with Someone who loves.